2021
DOI: 10.1038/s41598-021-82248-7
|View full text |Cite
|
Sign up to set email alerts
|

Second primary malignancies in colorectal cancer patients

Abstract: The prevalence of second primary malignancies (SPMs) in the western world is continually increasing with the risk of a new primary cancer in patients with previously diagnosed carcinoma at about 20%. The aim of this retrospective analysis is to identify SPMs in colorectal cancer patients in a single-institution cohort, describe the most frequent SPMs in colorectal cancer patients, and discover the time period to occurrence of second primary tumors. We identified 1174 patients diagnosed with colorectal cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…Compared with Sturludóttir et al, who analyzed the association between PC and rectal cancer over a period of 16 years, Jacobs et al reported a twofold higher incidence for synchronous PC and rectosigmoid cancer over a period of 20 years ( Jacobs et al, 2020 ; Sturludóttir et al, 2015 ). Another study from Czech Republic showed that 2.3% of patients diagnosed with CRC between 2003 and 2013 and followed until 2018 developed PC ( Halamkova et al, 2021 ), in line with a Swedish study that has shown that 1.9% of those over 72,000 patients have associated colon cancer and PC ( Van Hemelrijck et al, 2012 ). The incidence of 5% for D/MPMTs identified in our study is significantly higher compared with the aforementioned studies.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Compared with Sturludóttir et al, who analyzed the association between PC and rectal cancer over a period of 16 years, Jacobs et al reported a twofold higher incidence for synchronous PC and rectosigmoid cancer over a period of 20 years ( Jacobs et al, 2020 ; Sturludóttir et al, 2015 ). Another study from Czech Republic showed that 2.3% of patients diagnosed with CRC between 2003 and 2013 and followed until 2018 developed PC ( Halamkova et al, 2021 ), in line with a Swedish study that has shown that 1.9% of those over 72,000 patients have associated colon cancer and PC ( Van Hemelrijck et al, 2012 ). The incidence of 5% for D/MPMTs identified in our study is significantly higher compared with the aforementioned studies.…”
Section: Discussionsupporting
confidence: 60%
“…The incidence of D/MPMTs in which one of the tumors was PC varies between 1.14% ( Jin et al, 2014 ) and 8.7% ( Weir et al, 2013 ), while the cases in which one of the multiple tumors was a CRC had an incidence up to 19.9% ( Halamkova et al, 2021 ). A Dutch study that included almost 430,000 patients diagnosed with at least one form of cancer reported a prevalence of 7% for multiple malignancies, and 0.3% for the association of PC with CRC ( L. Liu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, a similar platinum-induced mutational load (430 SBSs) was previously reported in colon crypts of a single patient treated with cisplatin 24 . With an estimated 10 8 colorectal stem cells 25 in the adult colon, each platinum treatment leads to an enormous pool of potentially deleterious mutations that may explain why platinum drugs pose an increased risk for the development of secondary malignancies 26 .…”
Section: Characteristics Of Capox-induced Somatic Mutationsmentioning
confidence: 99%
“…The risk of secondary CRC amongst patients caused by first cancer radiotherapy treatment is an area of debate in clinical radiation oncology. The biggest challenge in evaluating the second CRC risk is the latency period of onset following initial radiotherapy treatment [46][47][48] . This recurrence is expected to occur many years after the first diagnosis 49 .…”
Section: Resultsmentioning
confidence: 99%